2022
DOI: 10.1038/s41386-022-01292-7
|View full text |Cite
|
Sign up to set email alerts
|

Insular cortex corticotropin-releasing factor integrates stress signaling with social affective behavior

Abstract: Impairments in identifying and responding to the emotions of others manifest in a variety of psychopathologies. Therefore, elaborating the neurobiological mechanisms that underpin social responses to social emotions, or social affective behavior, is a translationally important goal. The insular cortex is consistently implicated in stress-related social and anxiety disorders, which are associated with diminished ability to make and use inferences about the emotions of others to guide behavior. We investigated h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 60 publications
2
36
0
Order By: Relevance
“…We targeted the CRF system in this study because CRF is important for both social decision making (Rieger et al, 2022) and the social transfer of stress (Sterley and Bains, 2021; Sterley et al, 2018) -- two processes which we believe are prime targets to be affected by MIA which alters sociability and stress reactivity (Carlezon et al, 2019; Howerton and Bale, 2012; Zhao et al, 2021). Little is known about how the CRF system and CRF receptor distribution is affected by MIA (Perry et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We targeted the CRF system in this study because CRF is important for both social decision making (Rieger et al, 2022) and the social transfer of stress (Sterley and Bains, 2021; Sterley et al, 2018) -- two processes which we believe are prime targets to be affected by MIA which alters sociability and stress reactivity (Carlezon et al, 2019; Howerton and Bale, 2012; Zhao et al, 2021). Little is known about how the CRF system and CRF receptor distribution is affected by MIA (Perry et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Evoked field excitatory postsynaptic potentials (fEPSPs) were recorded on a 6 × 10 perforated multielectrode array (MCSMEA-S4-GR with 60pMEA100/30iR-Ti Array, Multichannel Systems) with integrated acquisition hardware (MCSUSB60) and analyzed with MC_RACK software (version 3.9) exactly as described previously (Rieger et al, 2022; Rogers-Carter et al, 2018). Slices were placed onto the array and affixed by downward suction through the perforated array.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both aIC and pIC neurons send projections to the BLA [30][31][32]. A recent study reported that CB1 receptors are expressed in IC glutamatergic neurons [42], but the distribution of CB1 receptors in axonal terminals of IC neurons is unclear. Interestingly, our targeted histological analyses revealed that CB1 receptors of IC neurons are intensively located on BLA but not CeA axon terminals.…”
Section: Dichotomy Of Insula Cb1 Receptors Expression On Ic Inputs To...mentioning
confidence: 99%
“…For example, deletions of either Fos or Stk11 in BLA-aIC neurons, alter intrinsic properties at the aIC, and impair CTA acquisition (Levitan et al, 2020). Furthermore, approach behaviors in social decision-making are modulated by subjective and sex-specific affective states that regulate cell-type-specific changes in intrinsic properties at IC terminals receiving hypothalamic input (Rogers-Carter et al, 2018, 2019; Rieger et al, 2022). The posterior IC (pIC) integrates visceral-sensory signals of current physiological states with hypothalamus-gated amygdala anticipatory inputs relating to food or water ingestion, to predict future physiological states (Livneh et al, 2017, 2020).…”
Section: Introductionmentioning
confidence: 99%